Filibuster obstruction and lawmaking in the U.S. Senate - Wawro, Gregory J. 1968-; Schickler, Eric 1969- (Princeton Univ. Press, 2006)
Parliamentary obstruction, popularly known as the 'filibuster,' has been a defining feature of the U.S. Senate throughout its history. In this book, Wawro and Schickler explain how the Senate managed to satisfy its lawmaking role during the 19th and early 20th centuy, when it lacked seemingly essential formal rules for governing debate. What prevented the Senate from self-destructing during this time? The authors argue that in a system where filibusters played out as wars of attrition, the threat of rule changes prevented the institution from devolving into parliamentary chaos. They show that institutional patterns of behavior induced by inherited rules did not render Senate rules immune from fundamental changes. The authors' theoretical arguments are supported through a combination of extensive quantitative and case-study analysis, which spans a broad swath of history. They consider how changes in the larger institutional and political context--such as the expansion of the country and the move to direct election of senators--led to changes in the Senate regarding debate rules. They further investigate the impact these changes had on the functioning of the Senate. The book concludes with a discussion relating battles over obstruction in the Senate's past to recent conflicts over judicial nominations.--Book jacket flap.
Includes bibliographical references (p. [285]-301) and index
Keywords: États-Unis - Congress - Senate - Règlements et procédure; United States -- Congress -- Senate -- Freedom of debate; United States -- Congress -- Senate -- Cloture; USA -- Congress; Obstructies; Obstructionnisme - États-Unis; Politieke oppositie; Senaat (Verenigde Staten); Wetgeving; Filibusters (Political science) -- United States; Gesetzgebung; Redefreiheit; Filibuster; Verenigde Staten; USA